Fruit scent as an evolved signal to primate seed dispersal - Nevo, Omer (Sci Adv, 2018)
The tremendous diversity of floral and fruit traits is, to a large extent, a set of adaptations that promote plant reproduction through animal pollinators and seed dispersers. Yet, it is still unknown whether fruit scent is a by-product of fruit maturation or an evolved communication channel with animal mutualists. We show that in species that specialize on seed dispersal by lemurs—an olfactorily oriented primate—fruits increase scent production and change their chemical composition significantly more than sympatric species whose seeds are largely dispersed by birds. We further show that lemurs use these shifts in fruit scent to identify ripe fruits. These results show that fruit scent is an evolved communication system that facilitates animal-plant mutualism.